2013 Business Plan - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The 2013 business plan of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) lays out the key activities in 2013, situated within the larger strategic framework of CCAFS.